Tribological performance and dry sliding-induced microstructure evolution in T20Z alloy under different atmospheric conditions. (23rd April 2020) - Zhong, H; Yang, L Q; Yue, Y; Ma, M Z; Jin, F X; Xiu, L
Abstract: This study focused on the tribological performance and microstructure evolution of T20Z alloy after dry sliding in air and vacuum. After the tribological tests, normal load and sliding velocity were considered to be optimized based on specific wear rates using Taguchi technique. The results of S/N ratio showed that the optimization of the parameters was 10 N, 0.59 m s −1 for obtaining the minimum wear rates in both air and vacuum. Also, the worn surface and cross-section of T20Z alloy as well as wear debris and counterpart steel balls were analyzed by scanning electron microscopy. Raman spectrometer was performed to further analyze the worn surface. The topography of wear scar was observed using a three-dimensional optical profilometer. The microstructure evolution of T20Z alloy was analyzed by transmission electron microscopy. The results showed that the wear mechanisms in air varied from abrasive wear to delamination wear and severe abrasive wear, and the grain size was finally refined to nanoscale. In vacuum, however, wear mechanisms changed from slight abrasive wear to delamination wear and severe plastic deformation, and only the β phase was deformed.